1998
DOI: 10.1177/10454411980090020301
|View full text |Cite
|
Sign up to set email alerts
|

Immune Defense Mechanisms of the Dental Pulp

Abstract: Defense reactions of the dentin/pulp complex involve a variety of biological systems, in which the immune system plays a pivotal role. The knowledge of the organization and function of pulpal immunocompetent cells has been sparse, but in recent years a significant body of information of immune mechanisms in general has provided a footing for substantial new knowledge of the immune mechanisms of the dental pulp. The identification of pulpal dendritic cells (DCs) has generated research activities which have led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
169
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(182 citation statements)
references
References 141 publications
(159 reference statements)
4
169
0
3
Order By: Relevance
“…When the enamel barrier is disrupted, the dentin exposed to the oral environment is degraded by Gram-positive bacteria, including streptococci, lactobacilli, and actinomyces, that largely dominate the carious lesion microflora (2). This leads to the development of inflammatory and immune events in the dental pulp, the molecular and cellular determinants of which remain unknown (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…When the enamel barrier is disrupted, the dentin exposed to the oral environment is degraded by Gram-positive bacteria, including streptococci, lactobacilli, and actinomyces, that largely dominate the carious lesion microflora (2). This leads to the development of inflammatory and immune events in the dental pulp, the molecular and cellular determinants of which remain unknown (3).…”
mentioning
confidence: 99%
“…They send long cytoplasmic processes into dentinal tissue. Thus, during dentin demineralization, bacteria and/or components released from their wall such as lipoteichoic acid (LTA) 2 (5,6) can gain access to odontoblasts (3). Therefore, they are the first cells encountered by bacteria entering dentin from the oral cavity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of microorganisms and their by-products (1,2), the root canal system infection produces a host response, which may clinically show the presence and development of periapical lesions (3,4). These microorganisms are a constant source of aggression and demand an inflammatory response (5).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent in vivo study also showed that MetaSEAL induced a milder neutrophil infiltration in rat subcutaneous tissue than a zinc oxide-eugenol sealer 8) . Major histocompatibility complex (MHC) class II molecule-expressing cells serve as antigen-presenting 26) . Therefore, the response of MHC class II molecule-expressing cells is a good indicator of a biomaterial's immunogenic potential 8) .…”
Section: Introductionmentioning
confidence: 99%